Routine ileal intubation in colonoscopy does not increase the polyp detection rate: a retrospective study - Wang, Weiyi; Chen, Ke; Xu, Ying; Zhou, Yufen; Chen, Ping (Zeitschrift für Gastroenterologie, 2020)
Colonoscopy is effective in the prevention and screening of colorectal cancer. Whether terminal ileal (TI) intubation is required during conventional colonoscopy and whether it offers clinical benefits with respect to polyp detection rate (PDR) remain unclear. This retrospective study included patients who underwent colonoscopy at our hospital between July 1, 2018 and April 20, 2019. The positive findings and time for TI intubation were recorded. Univariate and multivariate analyses were performed to identify factors associated with PDR. There were 1675 patients with cecal intubation colonoscopy, including 994 (59 %) with TI intubation and 8 (1 %) with intestinal disease. The mean time for TI intubation was 40 seconds (3–338), and the mean time from cecal intubation to arrival at the deep part of TI mucosa was 24 seconds (2–118). The overall PDR was 27 %. On multivariable analysis, age > 50 years [95 % confidence interval (CI) 2.837–4.590], male sex (95 %CI, 0.406–0.649), presence of symptoms (abdominal symptoms vs. asymptomatic, 95 % CI, 1.146–2.468; stool changes vs. asymptomatic, 95 % CI, 1.070–1.834), and non-TI intubation (95 % CI, 1.040–1.648) were independent predictors of higher PDR. Trend analysis indicated decreasing trend of PDR among non-TI intubation group, 0–5 cm TI intubation group, and > 5 cm TI intubation group (30 % vs. 27 % vs. 24 %, respectively; p < 0.05). TI intubation is necessary to identify small bowel disease among a designated population, but it was not suggested to be routinely performed as part of colonoscopy, owing to limited positive intestinal findings, extra time requirement, and possible PDR worsening.
Keywords: adenoma detection rate; colorectal cancer; polyp detection rate; screening colonoscopy; terminal ileal intubation